Analytical Performance Characteristics of the Accelerate Pheno™ System for Pathogen Identification and Susceptibility Testing for Gram-negative Bacteremia and Candidemia. (4th October 2017) - Burnham, Jason; Wallace, Meghan; Fuller, Brian; Burnham, Carey-Ann D; Kollef, Marin
Abstract: Background: The Accelerate Pheno™ system is a novel fast diagnostic that significantly reduces the time to ID and AST for GNB and ID of Candida spp. bloodstream infections, with the potential to impact clinical outcomes. Prospective clinical trials are needed to evaluate the impact of this new system on clinical outcomes and antimicrobial stewardship. Methods: From April 14, 2016 to March 3, 2017, blood cultures from unique patients in the emergency department and medical intensive care units at Barnes-Jewish Hospital that signaled positive and were Gram-stain positive for GNB or Candida spp. were eligible. AXDX testing using pre-FDA cleared software (v1.0) was conducted in parallel with standard-of-care (SOC) diagnostic testing. SOC AST was Kirby-Bauer Disk Diffusion and/or Etest ® and SOC ID was the VITEK ® MS system. Results: Of 341 screened blood culture bottles, 123 met inclusion criteria; 101 (82%) were on-panel for ID with AXDX, 88 GNB (7 species) and 13 C. glabrata or C. albicans . Non-panel organisms were other Candida spp. in 36.4% (8/22), other GNB in 54.5% (12/22), and Gram-positive bacteria in 9.1% (2/22). For on-panel organisms with MALDI-TOF as the gold standard, sensitivity for ID of GNB was 95.4%, specificity 99.9%. One each of the following was missed: E. coli, Klebsiella spp., Proteus spp., and P. aeruginosa . Of missed GNB, all except P. aeruginosa were part of polymicrobial cultures. For on-panel Candida spp., sensitivity of ID was 91.7%, specificity 99%. Overall category agreement (CA) for GNB AST between AXDX and SOC was 91.4%. CA was lowest for ampicillin-sulbactam (69.1%), piperacillin-tazobactam (85.7%), ceftazidime (86.4%), and tobramycin (87%). All other antibiotics had CA >92%. Very major errors were logged for 0.1% ( n = 1 for tobramycin), major errors for 1.5% ( n = 13), and minor errors for 6.3% ( n = 53). There were 13 assay failures, including 10 failed AST, 2 failed ID, and 1 instrument technical failure. The most common reason for failure was too few clones of bacteria for analysis using AXDX (9/13, 69.2%). Conclusion: The Accelerate Pheno TM system is a novel fast diagnostic with high sensitivity and specificity for the ID and AST of GNB and ID of Candida spp. bloodstream infections that are on-panel. Disclosures: C. A. D. Burnham, Accelerate Diagnostics: Investigator, Research support; M. Kollef, Accelerate Diagnostics: Consultant, Research support